Public perception of Malaysian government management during the first wave of COVID-19 outbreak - Aminudin, Rabi'ah; Lee, Pei May; Jamaiudin, Norhaslinda; Abdul Hamid, Rohana; Mohamad Shukri, Syaza Farhana (Emerald Publishing, 2023)
COVID-19 is a global pandemic that was unprecedented in human history. The scale of infection was unusual with most countries succumbing to this disease. Various mitigation plans were introduced by governments around the world to contain the spread of the virus. The Southeast Asian region is not spared from the harmful effects of COVID-19. Most Southeast Asian countries responded swiftly to COVID-19 by introducing stringent policies such as contact tracing, mandatory quarantine, restriction of movements, cancellation of public events, health screenings, and border closures early on to tackle the rapid spread of the virus. The adoption of technology for contact tracing such as MySejahtera (Malaysia), TraceTogether (Singapore), PeduliLindungi (Indonesia), Mor Chana (Thailand), and Stay Safe (Philippines) shows the rapid response from the governments to contain the spread of COVID-19. The variation in the degree of success stories at different timelines in managing COVID-19 in the region indicates that COVID-19 management requires short and long-term planning, especially in the public health policy. In the case of Malaysia, the first phase of movement control order (MCO, 18–31 March 2020) took place on the background of political turmoil. The newly formed government under the leadership of Muhyiddin Yasin announced the first phase of lockdown in Malaysia to control the rising number of COVID-19 cases. The lockdowns then evolved into different forms at different phases of implementation until it was announced on 8 March 2022 that the country is transitioning to the endemic phase on 1 April 2022. This study shows that the respondents to our survey during the first phase of MCO are highly aware of the government’s initiatives to manage COVID-19 and the Malaysian public has a high level of trust and confidence in the government’s initiatives. The stringent measures taken by the government in the first wave of COVID-19 were seen as a necessity and it provided legitimacy to the government despite being the first unelected government in Malaysian history.